PILOT STUDY OF THE UK "FLIPPED DISCHARGE" MODEL ADAPTED FOR USE IN A US ACADEMIC HEALTH SYSTEM. (16th November 2018) - Trotta, R; Shoemaker, A; Chancler, C; Greysen, R; Hudson, L; Meehan, P; Rushanan, S; Buccafuri, M
Abstract: Despite national attention to transitional care, hospital discharge and the post-acute period remain plagued by reports of poor patient and caregiver experiences, adverse events (medication errors and falls), delayed discharges, protracted length of stay, and avoidable hospital readmissions. The "Flipped Discharge" Model, developed in the UK, is an innovation whereby the patient's post-acute needs are assessed in the patient's own home rather than during hospital stay. Patients then receive immediate individualized interdisciplinary home-based interventions to maximize recovery and time spent at home by a singular care team across settings. This pilot study adapted the "Flipped Discharge" Model for use in a US academic medical center where handoff between hospital and home-based teams is required within current care delivery structure. Our model includes in-hospital comprehensive geriatric assessment, real-time communication between interdisciplinary team members across settings, day of discharge home nursing visit, medication delivery, and ongoing home-based therapy and social services. Over 6 months, 33 patients (average age=83, 70% female, 77% African American), were enrolled. Fidelity to the intervention components reached 90%. Length of stay decreased an average of 11 hours, time to first home visit decreased from 70 to 3.5 hours, and time to completion of home medication reconciliation decreased from 6 to 1.5 days. Patients, caregivers, and interdisciplinary staff across settings indicated acceptability of the pilot, citing improved patient-centeredness, work efficiency, and interdisciplinary collaboration. Next steps are to test this intervention to prevent post-acute institutionalization and unnecessary hospital readmissions, and support achievement of patient-centered goals in a larger controlled study.